Cytotoxic and apoptotic activities of the aqueous fruit extract of Passiflora edulis Sims var flavicarpa in an in vitro model of human colon cancer (2017)
ABSTRACT: Colorectal Cancer (CRC) is the fourth leading cause of cancer death in the world. Epidemiological studies have shown an association between CRC incidence/mortality with unhealthy dietary habits, which suggests the need to promote and protect health through the adoption of sustainable measures that allow the reduction of morbidity and mortality rates, such as the consumption of products of plant origin. Some phytochemicals derived from fruits have shown antiproliferative activity and high antioxidant capacity; however, few research advances have been obtained regarding the complex mixture of phytochemicals of certain fruits that could contain promising bioactive substances. For these reasons, in the present work we evaluated the cytotoxic activity and the pro-apoptotic potential of the aqueous extract of P. edulis Sims var. Flavicarpa on an in vitro CRC model. Chemical analysis of the extract was based on a preliminary phytochemical screening in which were identified metabolites such as phenolic compounds and sterols, which have displayed antitumoral properties. The extracts exerted cytotoxic and proapoptotic potential, demonstrated by the reduction on cell viability, increase of the SubG0/G1 cell populations and the positive staining with Annexin-V of treated cells. Our results suggest that P. edulis is a potential source of phytochemical compounds with cytotoxic and apoptotic potential over colon cancer cell lines.